B is for burka, C is for counterinsurgency: US troops experiences of and with Afghan society - Cosette, Sarah (AUC Knowledge Fountain, 2013)
Since 2001, members of the U.S. military and Afghan communities have been living alongside each other as part of the international political intervention and military campaign Operation Enduring Freedom. A schism occurred between Afghan societies in relation to this involvement, which in turn produced relationships between foreign troops and Afghan civilians, the state apparatus and insurgents. An international discourse of propaganda using gender as a tool surrounded the conflict and attempted to justify the presence of foreign militaries in Afghanistan by framing the U.S. as rescuers, liberating Afghan victims from Afghan oppressors. A counterinsurgency doctrine was developed after Afghanistan resisted the international hegemonic vision for the country, asking troops to battle for the hearts and minds of Afghans. U.S. troop’s reflections about their experiences in Afghanistan reveal a division in how these roles and relationships are imagined in the propaganda and doctrine and how they are experienced by the U.S. military’s service members. The relationship with Afghan communities is problematized and given context in this project as remembered and perceived by the U.S. troops. Representations were deconstructed and reconstructed by the troops revealing the perception of themselves and Afghans, the roles of the groups and the impact of foreign military presence in Afghanistan. Their identities develop while attempting to encourage hegemonic visions in the uniform of a foreign military other. U.S. troops perceptions are heavily influenced by media, propaganda and discourse, yet the reflections on their own experiences often question and challenge the realities of relationships between Afghans and themselves, blurring the lines between liberation and occupation.